Genetic differentiation of domesticated and wild common carps detected by three genetic analysis methods - XU Li-hua; LI Wei; WU chun-lin; DONG Zai-jie; WANG Cheng-hui (浙江大学学报. 农业与生命科学版)
Based on ten microsatellite loci, the three methods of principal coordinate analysis, Bayesian cluster analysis and genetic assignment techniques were used to detect genetic differentiation of the four domesticated populations (Xingguo red common carp, glass red common carp, purse red common carp and jian common carp) and two wild populations (distributed in two different sections of Yangtze River: Jianli in Hubei and Yangzhou in Jiangsu) of common carp (Cyprinus carpio L.). The principal coordinate analysis demonstrated that there was obvious genetic differentiation between domesticated and wild common carps, especially between purse red common carp and wild common carp that accounted for 48.23% of total variation according to the first and second principal components. The Bayesian cluster analysis showed four major genetic clusters among six populations, in which xingguo red common carp and the two wild common carp populations consisted of one cluster, and glass red common carp, purse red common carp and jian common carp consisted of one cluster, respectively. The Bayesian genetic assignment technique displayed high self-assignment accuracy for each population (81% -100%), especially for glass red common carp and purse red common carp (100% for each). The present study indicated that there were obvious genetic differentiations between the domesticated and wild common carps, and wild populations had been influenced by the domesticated strains. As a result, the three methods can effectively detect genetic differentiation not only among domesticated populations, but also between domesticated and wild common carps.